The cushioning effect of the measures adopted in Romania in response to the 2022 cost of living crisis - Antonio F. Amores; Georgiana Balaban; Silvia De Poli; Ioana Andrada Moldovan; Chrysa Leventi; Tamara Nae; Mattia Ricci (European Commission, Joint Research Centre (JRC), 2024)
In response to the energy crisis, which led to high inflation, Romania, like other EU Member States, introduced a series of price-related and income-related measures to cushion the negative impact on households' welfare. Using EUROMOD and its Indirect Tax Tool extension, we assess the impact of these measures on welfare across the income distribution, while distinguishing between automatic stabilisers and discretionary measures. We find that these measures did not succeed in diminishing entirely the negative effect of the inflationary shock on the lowest-income population, given that, on the one hand, the shock was higher for low-income deciles, and, on the other hand, the policies applied were not sufficiently targeted. Against this background, the use of targeted measures is warranted in order to improve the welfare effect of such measures on lower-income households and diminish income inequalities resulting from the energy crisis.
Keywords: 330; Energy supply; Shock; Inflation; Consumer price index; Low income; Social policy; Welfare analysis; Romania; Energieversorgung; Schock; Inflation; Verbraucherpreisindex; Niedrigeinkommen; Sozialpolitik; Wohlfahrtsanalyse; Rumänien